Political Analysis of Women Poll Workers Personal Challenges during General Elections-2024 in Pakistan: An exploratory study conducted in Malakand - Adeeba; Dr. Hussain Ali (Dialogue Social Science Review (DSSR), 2025)
Women poll workers play a vital role in conducting free and fair elections in Pakistan. The present study explored the personal challenges faced by women poll workers in Malakand. The study used qualitative research design with purposive sampling to conduct seven interviews with women poll workers. The study explored that women poll workers performed their elections duties as per the standards of Election Commission of Pakistan election rules in General Elections-2024. However, some of their personal issues were explored which hinder them to perform their official duty during elections. The study explored physical health, psychological issues with participants. Gender role was also explored as a personal challenge to them. In the study locale security concerns of women poll workers are also explored. The study concluded that women poll workers personal challenges should be considered and logistic support should be provided to enhance the women poll workers efficiency during elections duty.